2013
DOI: 10.1177/1065912913508011
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the “Palin Effect” in the 2008 U.S. Presidential Election

Abstract: “The ‘Palin Effect’ in the U.S. 2008 Presidential Election” analyzes the effect of Sarah Palin on presidential vote choice. Two of the substantive conclusions are (1) Palin cost McCain votes among independents and moderates, and (2) Palin had the largest effect on vote choice of any recent vice-presidential nominee. Our analysis shows that the data do not support these findings. We find that respondent evaluations of Palin have a positive effect on McCain vote choice, even among independents and moderates, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…However, I respectfully disagree with their conclusions. They argue that they challenge the finding in my original article that there was "a negative conditional effect of feelings toward Palin on the likelihood of a McCain vote among independents and moderates" (Burmilla and Ryan 2013). This is not what I argued.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…However, I respectfully disagree with their conclusions. They argue that they challenge the finding in my original article that there was "a negative conditional effect of feelings toward Palin on the likelihood of a McCain vote among independents and moderates" (Burmilla and Ryan 2013). This is not what I argued.…”
Section: Discussionmentioning
confidence: 85%
“…The marginal effect entails a test of the hypothesis that compared with prior vice-presidential nominees, Palin produced a weaker (not stronger) effect on vote choice. This appears to be the basis of Burmilla and Ryan's (2013) criticism of my original article that "the positive coefficient on the Palin thermometer variable, undermines the conclusion that Palin cost McCain votes." Surely-and no matter the conditioning variable noted by Burmilla and Ryan-as Palin's feeling thermometer increases, the probability of a McCain vote will go up too.…”
Section: What Is the Palin Effect?mentioning
confidence: 82%
See 2 more Smart Citations
“…Pomper (2010, 59) reported that McCain won only 32% of the vote among those who expressed this concern. Palin’s perceived lack of qualifications and high name recognition may have cost McCain among independent voters (Knuckey 2012), although some scholars contend that the “Palin Effect” was negligible and consistent with other presidential races (Burmila and Ryan 2013). Even then, Obama’s large victory and McCain’s other liabilities cast doubt about whether he could have beaten Obama—even with a different running mate besides Palin.…”
Section: Favorite Sons and Daughters: The Vice-presidential Bumpmentioning
confidence: 99%